Identification of prognostic markers in diffuse midline gliomas H3K27M‐mutant. (14th August 2019) - Dufour, Charlotte; Perbet, Romain; Leblond, Pierre; Vasseur, Romain; Stechly, Laurence; Pierache, Adeline; Reyns, Nicolas; Touzet, Gustavo; Le Rhun, Emilie; Vinchon, Matthieu; Maurage, Claude‐Alain; Escande, Fabienne; et al.
Abstract: Pediatric diffuse midline gliomas are devastating diseases. Among them, diffuse midline gliomas H3K27M‐mutant are associated with worse prognosis. However, recent studies have highlighted significant differences in clinical behavior and biological alterations within this specific subgroup. In this context, simple markers are needed to refine the prognosis of diffuse midline gliomas H3K27M‐mutant and guide the clinical management of patients. The aims of this study were (i) to describe the molecular, immunohistochemical and, especially, chromosomal features of a cohort of diffuse midline gliomas and (ii) to focus on H3K27M‐mutant tumors to identify new prognostic markers. Patients were retrospectively selected from 2001 to 2017. Tumor samples were analyzed by immunohistochemistry (including H3K27me3, EGFR, c‐MET and p53), next‐generation sequencing and comparative genomic hybridization array. Forty‐nine patients were included in the study. The median age at diagnosis was 9 years, and the median overall survival (OS) was 9.4 months. H3F3A or HIST1H3B mutations were identified in 80% of the samples. Within the H3K27M‐mutant tumors, PDGFRA amplification, loss of 17p and a complex chromosomal profile were significantly associated with worse survival. Three prognostic markers were identified in diffuse midline gliomas H3K27M‐mutant: PDGFRA amplification, loss of 17p and a complex chromosomal profile. These markers are easy to detect in daily practice and should be considered to refine the prognosis of this entity.